Efektivitas Metode Dialog Sokratik untuk Mengembangkan Keterampilan Berpikir Kritis - Novianti, Williya; Siddik, Riesa Rismawati; Suherman, Maya Masyita; Pahlevi, Reza (Universitas Mathla'ul Anwar Banten, 2023)
Critical thinking skills, is an important asset that students must have as a provision for dealing with technological developments and the effects of globalization in the era of disruption towards the era of society 5.0. One effort to develop students' critical thinking skills is through the socratic dialogue method. In general, this study aims to find out how the effectiveness of the socratic dialogue method can develop the critical thinking skills of students in class XI IPS at SMA Negeri 1 Batujajar in 2022-2023. The research approach uses a quantitative approach with experimental methods, non-equivalent control-group design. Sampling technique using non-probability homogenous sampling technique on 162 students of class XI IPS SMAN 1 Batujajar. Data collection uses a measuring tool in the form of a critical thinking skills test instrument. The results of the study show: (1) the profile of students' critical thinking skills is generally in the medium category; (2) the socratic dialogue method is effective for developing critical thinking skills; (3) all aspects of critical thinking skills experience a significant increase in value with the treatment of the socratic dialogue method.